Evaluation of the state of dentition in children and adolescents aged 16-18 attending secondary schools in the city of Lublin - Krawczyk, Dorota; Pels, Elżbieta; Jędrych, Marian; Błaszczak, Jerzy (Polish Journal of Public Health, 2012)
Introduction. Epidemiological studies are an important tool used to monitor and ultimately to limit pathological processes in the oral cavity.Aim. The aim of the study was to evaluate the state of dentition in children and adolescents aged 16-18 attending secondary schools in the city of Lublin.Material and methods. The study included 300 children, i.e. 100 children aged 16, 100 aged 17 and 100 aged 18. DMF, D, M, F, OHI-S indices were determined, as well as the treatment index TI. For all schools, the study was conducted in the dentist’s office operating on the school premises. In each school, the dentist’s office had been operating in the school for more than 5 years. The study results were recorded in the study card according to the WHO guidelines.Results. A statistical analysis showed that in the group of 16-year-olds, statistical differences were recorded between boys and girls with respect to FT (T=2.262, S=0.024) and TI (T=1.94, S=0.050), and in the group of 17-year-olds statistical differences were observed with respect to the DMFT value (T=3.690, S=0.0002), DT (T=2.117, S=0.034), FT (T=2.583, S=0.010), DMFS (T=3.788, S=0.0002), DS (T=2.513, S=0.012), and FS (T=2.958, S=0.003).In the group of 18-year-olds, no statistical differences were observed between boys and girls with respect to the study parameters. A comparison of particular age groups showed significant differences in the DMFT (T=1.973, S=0.049) and DMFS (T=1.994, p=0.046) values.Conclusions. The study results showed high values of the caries index and low values of the treatment index in all the study groups and lower values of caries index among girls than boys.